Telocytes in the human ascending aorta: Characterization and exosome‐related KLF‐4/VEGF‐A expression. Issue 20 (25th September 2021) - Aschacher, Thomas; Schmidt, Katy; Aschacher, Olivia; Eichmair, Eva; Baranyi, Ulrike; Winkler, Bernhard; Grabenwoeger, Martin; Spittler, Andreas; Enzmann, Florian; Messner, Barbara; Riebandt, Julia; Laufer, Guenther; et al.
Abstract: Telocytes (TCs), a novel interstitial cell entity promoting tissue regeneration, have been described in various tissues. Their role in inter‐cellular signalling and tissue remodelling has been reported in almost all human tissues. This study hypothesizes that TC also contributes to tissue remodelling and regeneration of the human thoracic aorta (HTA). The understanding of tissue homeostasis and regenerative potential of the HTA is of high clinical interest as it plays a crucial role in pathogenesis from aortic dilatation to lethal dissection. Therefore, we obtained twenty‐five aortic specimens of heart donors during transplantation. The presence of TCs was detected in different layers of aortic tissue and characterized by immunofluorescence and transmission electron microscopy. Further, we cultivated and isolated TCs in highly differentiated form identified by positive staining for CD34 and c‐kit. Aortic‐derived TC was characterized by the expression of PDGFR‐α, PDGFR‐β, CD29/integrin β‐1 and αSMA and the stem cell markers Nanog and KLF‐4. Moreover, TC exosomes were isolated and characterized for soluble angiogenic factors by Western blot. CD34 + /c‐kit + TCs shed exosomes containing the soluble factors VEGF‐A, KLF‐4 and PDGF‐A. In summary, TC occurs in the aortic wall. Correspondingly, exosomes, derived from aortic TCs, contain vasculogenesis‐relevant proteins. Understanding the regulation of TC‐mediated aortic remodelling may be a crucial step towards designing strategies to promote aortic repair and prevent adverse remodelling.